Development of integrated system of computer monitoring of systems of automatic landing of planes during operation stage - Зеленков, О. А.; Масловеький, Б. Г. (Proceedings of National Aviation University (archive), 2002)
The application of algorithms for obtaining statistical estimations of airborne landing parameters during computer monitoring of the state of automatic landing systems during operation is considered.